Mitigating Disadvantage: Effects of Small-Scale Schooling on Student Achievement in Alaska - Gary Huang; Craig Howley (Journal of Research in Rural Education, 1993)
Controlling for three domains of background variables (school resources, school climate, and student academic background), this study investigated the hypothesis that school size mediates the effect of disadvantaged status on the achievement of individual students. The group studied included all students in grades 4 (N =5,589), 6 (N =3,930), and8 (N =4,034) whohadcontinuously attended the sameschool district for at least four years prior to their participation in the fall 1989 Alaska Statewide Student Testing Program. Data were analyzed with multiple regression analysis with three domains of background variables controlled. Results indicated that, although the average achievementscore was lower for students in small schools than in large schools, (a) the negative effect of disadvantaged background on student achievement wassignificantly less in small than in medium orlarge schools and (b) the interaction of disadvantaged status and school size explains additional variance in student achievement.